Dark Continents : Psychoanalysis and Colonialism - Khanna, Ranjana, 1966- (Book collections on Project MUSE., 2003)
Argues that the psychoanalytic self was constituted through the specifically national-colonial encounters of the late 19th and early 20th centuries, and that therefore somewhat paradoxically perhaps, psychoanalysis is crucial for understanding postcolonial, feminist theory.